Original paperTHE ASSOCIATION BETWEEN ACE GENE VARIATION AND AEROBIC CAPACITY IN WINTER ENDURANCE DISCIPLINES - Orysiak, J.; Zmijewski, P.; Klusiewicz, A.; Kaliszewski, P.; Malczewska-Lenczowska, J.; Gajewski, J.; Pokrywka, A. (Biology of Sport, 2013)
The aim of the study was to examine the possible relationship between I/D polymorphism of ACE gene and selected indices of aerobic capacity among male and female athletes practising winter endurance sports. Sixty-six well-trained athletes (female n=26, male n=40), aged 18.4 ± 2.8 years, representing winter endurance sports (cross-country skiing, n=48; biathlon, n=8; Nordic combined, n=10) participated in the study. Genotyping for ACE I/D polymorphism was performed using polymerase chain reaction. Maximal oxygen consumption (VO2max), maximal running velocity (Vmax) and running velocity at anaerobic threshold (VAT4) were determined in an incremental test to volitional exhaustion on a motorized treadmill. The ACE genotype had no significant effect on absolute VO2max, relative VO2max (divided by body mass or fat free body mass), VAT4 or Vmax. No interaction effect of gender x ACE genotype was found for each of the examined aerobic capacity indices. ACE gene variation was not found to be a determinant of aerobic capacity in either female or male Polish, well-trained endurance athletes participating in winter sports.